Management of Student Character Education Through Cheerleading Extracurricular Activities in the City of Surabaya (Multi-Site Study at SMPN 17 and SMPN 12 Surabaya) - Kristiani, Lucia Ayu; Karwanto, Karwanto; Khamidi, Amrozi (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to explore the management of cheerleading extracurricular activities in fostering students’ character at SMP Negeri 12 Surabaya and SMP Negeri 17 Surabaya. Employing a qualitative approach with a multi-site case study design, the research focuses on understanding how schools organize, implement, and evaluate cheerleading programs to develop values such as discipline, responsibility, cooperation, leadership, and sportsmanship. Data were collected through participant observation, in-depth interviews with students, coaches, and school principals, as well as document analysis. The analysis was conducted using a descriptive-inductive method involving data reduction, presentation, and verification. To ensure data validity, triangulation of sources and methods, prolonged observation, and thorough examination were applied. Findings indicate that cheerleading extracurricular activities contribute significantly to character development by providing opportunities for students to practice collaboration, responsibility, and leadership in authentic contexts. The study also identifies supporting and inhibiting factors that affect the effectiveness of character education through these activities.